1999
DOI: 10.2307/2676329
|View full text |Cite
|
Sign up to set email alerts
|

Civil War, Social Integration and Mental Health in Croatia

Abstract: Research has shown that social relationships are generally beneficial for mental health (Thoit s 1995). However, few scholars have examined this association after the occurrence of a significant shoc k to the social system as a whole. The purpose of this article is to examine the relationship between socia l integration and war-related distress in Croatia immediately following the recent civil war. Does social integration decrease war-related distress? Does social integration buffer the effect of traumatic eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
48
2
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(58 citation statements)
references
References 44 publications
7
48
2
1
Order By: Relevance
“…Prior research involving Indigenous groups in Australia and internationally suggests that kinship connections can result in sharing the psychological and physical burdens of more people (Brough et al, 2004;Richmond and Ross, 2008). In challenging situations, such as those created by poverty or discrimination, bonded relationships can have a detrimental effect upon individuals' physical and psychological resources (Browne-Yung et al, 2013;Kunovich and Hodson, 1999;Mitchell and Mark, 2002;Richmond and Ross, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Prior research involving Indigenous groups in Australia and internationally suggests that kinship connections can result in sharing the psychological and physical burdens of more people (Brough et al, 2004;Richmond and Ross, 2008). In challenging situations, such as those created by poverty or discrimination, bonded relationships can have a detrimental effect upon individuals' physical and psychological resources (Browne-Yung et al, 2013;Kunovich and Hodson, 1999;Mitchell and Mark, 2002;Richmond and Ross, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…We expect direct war experiences, events the respondents personally witnessed, directed at themselves, their family, or community, to have a stronger impact on war-related distress than events experienced indirectly, that is, events they were told about but did no personally witness (Basoglu et al, 2005;Kunovich & Hodson, 1999).…”
mentioning
confidence: 99%
“…Earlier research identified a range of socioeconomic risk factors in developing posttraumatic stress symptoms (Kunovich & Hodson, 1999;Powell, Rosner, Butollo, Tedeschi, & Calhoun, 2003;Silove, 1999): female gender, older age, lack of social support, low socioeconomic status, low level of education, and urban location. There is a rich literature on social inequalities in general health pointing to parallel differences (Kunst et al, 2005;Cavelaars et al, 1998;Bartley, 2004).…”
mentioning
confidence: 99%
“…In this instance, the success of governmental policy initiatives appears to be dependent on the actions of vulnerable individuals living in socially disadvantaged communities. Kunovich and Hodson (1999) carried out research on participation in social groups and psychological well-being in postwar Croatia. Mixed results were recorded.…”
Section: Problematic Issues Of Social Capital Theorizing and Psycholomentioning
confidence: 99%